The place is in the collection sakakin harir of Hamid AL- Zamili - Mr. Salim Khamees Hadi Al-Hadidi (Journal of College of Education, 2025)
Place is one of the pillars of the main narrative. Without place, there is no complete narrative work. It adds adornment and beauty to the work, and leaves a clear imprint on it. The writer’s movement between places, and the artistry he uses, makes the recipient’s mind tense, as he moves with him from one place to another, in this research of mine. I dealt with time in the collection of stories by the writer Hamid Al-Zamili. He is an Iraqi writer known for his narrative works. He knows how to place words in the right place so that the text comes out to the recipient in its most beautiful form. The research was divided into an introduction and a conclusion. In the introduction, I dealt with a summary of the of place in the Arabic story. The conclusion came in the most important results of the research. The researcher divided the research into two sections. The first section was titled (The Open and Closed Place), while the second section was titled (Description of the Place)